PENGARUH INTENSITAS KOMPETISI PASAR TERHADAP KINERJA MANAJER UKM MELALUI INFORMASI SISTEM AKUNTANSI MANAJEMEN - Alliyah, Siti; Hidayat, Riskin (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.08.TAHUN 2015, 2015)
This research aims to test the effect of the intensity of market competition on the performance of SMEs managers through the Management Accounting System (MAS) information. This research use survey method with sampel is Small and Medium Enterprises (SMEs) in Kabupaten Rembang, with cluster sampling obtained sample 207 SMEs. Analysis of the data using Path Analysis. Result of research refer that intensity of market competition have an influence on significant positive to MAS and MAS have an influence on significant positive to the performance of SMEs managers, but the intensity of market competition is not significant positive effect on the performance of SMEs managers. This suggest that SAM can mediate the relationship between the intensity of market competition with the performance of SMEs managers.
Keywords: intensity of market competition, Management Accounting System (MAS), information performance of SMEs managers